Spiritual care competence for contemporary nursing practice: a quantitative exploration of the guidance provided by fundamental nursing textbooks - TIMMINS, FIONA; BEGLEY, THELMA; SHEAF, GREG; NEILL, FREDA; MURPHY, MARYANNE (My University, 2015)
Spirituality is receiving unprecedented attention in the nursing literature. Both the volume and scope of literature on the topic is expanding, and it is clear that this topic is of interest to nurses. There is consensus that the spiritual required by clients receiving health ought to be an integrated effort across the health care team. Although undergraduate nurses receive some education on the topic, this is ad hoc and inconsistent across universities. Textbooks are clearly a key resource in this area however the extent to which they form a comprehensive guide for nursing students and nurses is unclear. This study provides a hitherto unperformed analysis of core nursing textbooks to ascertain spirituality related content. 548 books were examined and this provides a range of useful information about inclusions and omissions in this field. Findings revealed that spirituality is not strongly portrayed as a component of holistic care and specific direction for the provision of spiritual care is lacking. Fundamental textbooks used by nurses and nursing students ought to inform and guide integrated spiritual care and reflect a more holistic approach to nursing care. The religious and/or spiritual needs of an increasingly diverse community need to be taken seriously within scholarly texts so that this commitment to individual clients' needs can be mirrored in practice.
PUBLISHED
Keywords: Textbooks; Spiritual care competencies; Spirituality; Nursing; Nurses; Nursing Education